The Effectiveness of Employee Performance at the Kelapa Lima Sub-District Office Merauke Regency - Nur Jalal; Agustina Wogan; Syahrabudin Husein Enala (PAPSEL Research and Consulting, 2024)
The Effectiveness of Employee Performance at the Kelapa Lima Sub-District Office, Merauke Regency. This study aims to evaluate the effectiveness of employee performance at the Kelapa Lima Sub-District Office, Merauke Regency. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and document analysis. The findings indicate that employee performance is generally good but not yet optimal. The organizational characteristics show that duties and functions have been carried out properly, although challenges remain, particularly regarding employee capabilities, which affect the timeliness of task execution. The work environment is divided into external and internal environments. The external environment, which includes factors outside the organization, influences decision-making and organizational actions. The internal environment, which encompasses the organizational climate, plays a crucial role in the overall functioning of the organization. Regarding employee characteristics, there is a variation in educational levels and employee competencies, which contribute to delays in completing tasks. Efforts to improve performance are being made through training provided by the sub-district head, which gradually helps employees master their duties.